Fuzzy representation of rainfall threshold in triggering mass removal processes - González-Campos, José; Romero-González, Carlos; Carvajal-Muquillaza, Cristian (Uniciencia, 2021)
The main objective of this research is to implement a new methodology for the quantitative representation of metric records on mass removal processes that incorporates the characteristic imprecision consistent with human and/or technical nature. The research used a positivist paradigm with a quantitative scope and longitudinal measurement in a propositive context. The study sample included daily rainfall records of the Punta Ángeles meteorological stations from the Chilean Navy Meteorological Service and Meteorological Laboratory of the Institute of Geography of the Pontifical Catholic University of Valparaiso, between 2008 and 2013. As a result, it is observed that the proposed methodology allows for quick decision-making with formal statistical support, as well as consistency in the precipitation measurements from both stations. In addition, the creation of an alert threshold was improved, and no significant differences were established in the rainfall variability in the meteorological stations studied and the recording years, which leads to the conclusion that this proposal represents a qualitative improvement in generating quantitative results.